THE IMPACT OF THE EQUITY CAPITAL AND TRADE CREDIT FINANCIAL SOURCES ON THE COMPANYS PERFORMANCES SUSTAINABILITY - Milosević, Dragan; Popović, Jovanka; Avakumović, Jelena; Kvrgić, Goran (Economics of Agriculture, 2020)
The crucial aspect of mobilizing financial sources and savings to SMEs in the agribusiness sector and its supply chains towards sustainability and productive investment is of the most importance, what has motivated the research of this paper. Key findings of exploring the impact of two external sources of finance, trade credit and equity capital on the sustainability of the enterprises, are based on the literature review and the empirical research provided in Serbia in 2019. The positive influence of the researched sources of the financing as well as the conditions of this financing on the sustainability of these enterprises is confirmed. The contribution of the research results can be seen in the further improvement of the financial market framework for development of the external sources of finance, trade credit and equity capital in the context of entrepreneurial finance.